Association Between Language Use and ICU Transfer and Serious Adverse Events in Hospitalized Pediatric Patients Who Experience Rapid Response Activation - McDade, Jessica E.; Olszewski, Aleksandra E.; Qu, Pingping; Ramos, Jessica; Bell, Shaquita; Adiele, Alicia; Roberts, Joan; Coker, Tumaini R. (Frontiers in Pediatrics, 2022)
Background: Hospitalized patients and caregivers who use a language other than English have worse health outcomes, including longer length of stay, more frequent readmissions, and increased rates of in-hospital adverse events. Children who experience clinical deterioration (as measured by a Rapid Response Team event) during a hospitalization are at increased risk for adverse events and mortality. Methods: We describe the results of a retrospective cohort study using hospital records at a free-standing, quaternary children’s hospital, to examine the association of language of care with outcomes (transfer to intensive care, adverse event, mortality prior to discharge) following Rapid Response Team event, and whether increased interpreter use among patients who use a language other than English is associated with improved outcomes following Rapid Response Team event. Results: In adjusted models, Rapid Response Team events for patients who use a language other than English were associated with higher transfer rates to intensive care (RR 1.1, 95% CI 1.01, 1.21), but not with adverse event or mortality. Among patients who use a language other than English, use of 1-2 interpreted sessions per day was associated with lower transfer rates to intensive care compared to use of less than one interpreted session per day (RR 0.79, 95% 0.66, 0.95). Conclusion: Rapid Response Team events for hospitalized children of families who use a language other than English are more often followed by transfer to intensive care, compared with Rapid Response Team events for children of families who prefer English. Improved communication with increased interpreter use for hospitalized children who use a language other than English may lead to improvements in Rapid Response Team outcomes.